Ecosystem Services for Spatial Planning Innovative Approaches and Challenges for Practical Applications - Ronchi, Silvia (Green Energy and Technology,, 2018)
The book investigates the relationship between ecosystem services (ES) and spatial planning, and explores potential means of integrating the two concepts to support the decision-making process. In addition, it presents case studies demonstrating the outcomes, limitations, opportunities and further new developments in ES assessment/mapping for planning support. Then it describes the "Restart from Ecosystem Services" (RES) methodology, which is aimed at integrating ES into the planning process using an ecological balance, and at promoting new planning parameters for the transformation areas. RES ensures the inclusion of ES in planning processes using the incremental measures of limiting, mitigating and compensating soil sealing and land take process promoting operational strategies in applying it. The implementation of RES is associated with strategic environmental assessment and provides valuable support in the definition of strategies across the entire planning process, especially for the evaluation of alternative scenarios.